A Case Study Of The Effectiveness Of Therapy Benson In Lowering Blood Pressure In The Elderly With Hypertension In Suntalangu Village: Studi Kasus Efektivitas Trapi Benson Dalam Menurunkan Tekanan Darah Pada Lansia Dengan Hipertensi Di Desa Suntalangu - Irwansyah Irwansyah; Ahyar Rosidi (Journal of Health and Physical, 2025)
Hypertension is one of the chronic health problems that are often experienced by the elderly and is known as the silent killer because it can cause serious complications such as stroke, heart disease, and kidney failure. Hypertension is treated not only through pharmacological therapy, but also through non-pharmacological interventions, one of which is with the Benson relaxation technique, which is proven to help lower blood pressure through the body's relaxation mechanism and stress reduction. This study aims to determine the effectiveness of Benson's relaxation therapy in lowering blood pressure in elderly people with hypertension. The research design uses case studies with a nursing process approach that includes assessment, diagnosis, planning, implementation, and evaluation. The study was conducted on an elderly person with hypertension in Suntalangu Village, Suela District for 3 x 24 hours. The research instrument is a sphygmomanometer to measure blood pressure. The results of the initial assessment showed that the patient's blood pressure was 170/90 mmHg with complaints of headache, fatigue, and pain in the back of the head. After regular Benson relaxation therapy for 3 days, there was a decrease in blood pressure to 150/80 mmHg with reduced pain complaints and the patient appeared more relaxed. The evaluation showed that there was an improvement in the patient's physical and psychological condition as well as the patient's ability to relax independently. Benson relaxation therapy is effective in lowering blood pressure in the elderly with hypertension and can be used as a simple, safe, and independent non-pharmacological intervention to improve the quality of life of people with hypertension.